A systemically administered detoxified TLR4 agonist displays potent antitumor activity and an acceptable tolerance profile in preclinical models - Chettab, Kamel; Fitzsimmons, Chantel; Novikov, Alexey; Denis, Morgane; Phelip, Capucine; Mathé, Doriane; Choffour, Pierre Antoine; Beaumel, Sabine; Fourmaux, Eric; Norca, Patrick; Kryza, David; Evesque, Anne; et al. (Frontiers in Immunology, 2023)
Bacterial lipopolysaccharides (LPS) are potent innate immunostimulants targeting the Toll-like receptor 4 (TLR4), an attractive and validated target for immunostimulation in cancer therapy. Although LPS possess anti-tumor activity, toxicity issues prevent their systemic administration at effective doses in humans. We first demonstrated that LPS formulated in liposomes preserved a potent antitumor activity per se upon systemic administration in syngeneic models, and significantly enhance the antitumor activity of the anti-CD20 antibody rituximab in mice xenografted with the human RL lymphoma model. Liposomal encapsulation also allowed a 2-fold reduction in the induction of pro-inflammatory cytokines by LPS and. Mice receiving an intravenous administration demonstrated a significant increase of neutrophils, monocytes and macrophages at the tumor site as well as an increase of macrophages in spleen. In a second step, we demonstrated that the encapsulation of chemically detoxified LPS (MP-LPS) in a clinically approved liposomal formulation further reduced its toxicity, notably its pyrogenicity (10-fold) as well as the induction of proinflammatory cytokines, while maintaining a potent antitumor activity per se and a strong immunoadjuvant effect. This improved tolerance profile of liposomal MP-LPS was associated with the preferential activation of the TLR4-TRIF pathway. Finally, in vitro studies demonstrated that stimulation with encapsulated MP-LPS reversed the polarization of M2 macrophages towards an M1 phenotype, and a phase 1 trial in healthy dogs validated its tolerance upon systemic administration up to very high doses (10µg/kg). Altogether, our results demonstrate the strong therapeutic potential of MP-LPS formulated in liposomes as a systemically active anticancer agent, supporting its evaluation in patients with cancer.